PERGESERAN PERAN NINIK MAMAK DIBIDANG KESENIAN (CALEMPONG,BADIKIU, ALBARZANJI ) DIDESA BINAMANG KEC.XIII KOTO KAMPAR KAB.KAMPAR - Ahmad Fauzan; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Artistry or proprietary tradition by a region constitutes proprietary alone pride by that region, and its equitable keeps up and be kept one can maybe. Since a tradition until whenever if is kept up will that mengharumkan can ever region even this nation. As one we knows our State which is the loved one Indonesia State this rich will tradition, tradition or culture even that can pride us winked by the world. Penelitan this was done to know ninik mamak's role in customs terminological artistry which apply at Binamang's village, and Whatever ninik mamak's role in artistry area that experience change at silvan Binamang, and the latest For Whats factor that cause changed on ninik mamak's role in artistry at silvan Binamang. Respondent in observational it is ninik mamak in yanga's terms is at binamang But disina is researcher just takes four tribe that is made as respondent which is Paduko Rajo's Malay tribe, Sinaro's malay, Caniago, and Pitopang.Observational location to be done at binamang's village Koto Kamapar's XIII district, writer will work through ninik mamak's role shift in artistry area at silvan Binamang. To get needful data deep observational it, writer gathers data by interview wield kuisoner's list. Data that is gotten succeeding at o in analisis kualitatif, which is successful data afters gathered by data at o and sorted bases its type and then explained by descriptive ala which is is explained deep shaped word so depicts particular situation of binamang's village society which is about role ninik mamak and its shift.Therefore conclusion of this research is tradition tradition shift artistry that is at binamang's village because of was beginning reducing the ninik mamak's role in hands down or this tradition, besides epoch developing that progressively quick one begets cousin child can't utterly dikotrol by ninik mamak they.Key word: Ninik Mamak's role, Artistry, Binamang's village